China, the developing world, and the new global dynamic - Dittmer, Lowell (ed.); Yu, George T. (ed.) (New Delhi, 2012)
With China's rise as a major player in international affairs, how have its policies toward developing countries changed? And how do those policies now fit with its overall foreign policy goals? This timely new book explores the complexities of China's evolving relationship with the developing world. The authors first examine the political and economic implications of China's efforts to be seen as a responsible great power. A series of comprehensive regional chapters then showcase a quid pro quo relationship - variously involving crucial raw materials, energy, and consumers on the one hand and infrastructure development, aid, and security on the other. The concluding chapter illuminates China's search for national identity in the context of widespread suspicions of its strategic motives. The result is a thorough, yet accessible, view of an increasingly important topic in global affairs. This book explores the complexities of China's evolving relationship with the developing world, including countries in Africa, Asia, the Middle East, and Latin America.
Keywords: China-Foreign economic relations-Developing countries